PROTOTIPE RANCANG BANGUN PINTU BENDUNGAN OTOMATIS UNTUK IRIGASI PERTANIAN BERBASIS MIKROKONTROLER ARDUINO ATMEGA328 - iman permana (Fakultas Ilmu Komputer, Unversitas Muhammadiyah Riau, 2020)
Technology as a result of human inventions to facilitate the work of increasingly advanced human technology and the development of various kinds of innovations especially developments in the field of microcontroller technological inventions penetrated various aspects ranging from transportation medicine and agriculture The large number of residents who use hydropower dams as water storage Open and close water dam gates automatically are buildings and structures that can function to open and close the flow of water to the river upstream according to the water level at the headwaters or dams. This tool uses the principle water level control work for water level detection using ultrasonic sensors with the design of this tool can then make it easier in terms of monitoing in opening and opening the water dam door automatically so as to facilitate in regulating the flow of water discharge without having to use a guard by adding an LCD to make it easier to show water level information and alarms on dams that can change in an uncertain period of time and then discharge reportsthe height of the water can be seen through the web so that it can facilitate and reduce a human error factor human error